Crystal structures of (RS)-N-[(1R,2S)-2-benzyloxy-1-(2,6-dimethylphenyl)propyl]-2-methylpropane-2-sulfinamide and (RS)-N-[(1S,2R)-2-benzyloxy-1-(2,4,6-trimethylphenyl)propyl]-2-methylpropane-2-sulfinamide: two related protected 1,2-amino alcohols - Matthew R. Carbone; Garrick A. Centola; Adam Haas; Kevin P. McClelland; Michael D. Moskowitz; Angelo M. Verderame; Mikael S. Olezeski; Louis J. Papa; Stephanie C. M. Dorn; William W. Brennessel; Daniel J. Weix (Acta Crystallographica Section E, 2014)
The title compounds, C22H31NO2S, (1), and C23H33NO2S, (2), are related protected 1,2-amino alcohols. They differ in the substituents on the benzene ring, viz. 2,6-dimethylphenyl in (1) and 2,4,6-trimethylphenyl in (2). The plane of the phenyl ring is inclined to that of the benzene ring by 28.52 (7)° in (1) and by 44.65 (19)° in (2). In the crystal of (1), N—H...O=S and C—H...O=S hydrogen bonds link molecules, forming chains along [100], while in (2), similar hydrogen bonds link molecules into chains along [010]. The absolute structures of both compounds were determined by resonance scattering.